Neural Correlates of Repetition Priming: A Coordinate-Based Meta-Analysis of fMRI Studies - Lee, Sung-Mu; Henson, Richard N.; Lin, Chun-Yu (Frontiers in Human Neuroscience, 2020)
Repetition priming is a form of implicit memory, whereby classification or identification of a stimulus is improved by prior presentation of the same stimulus. Repetition priming is accompanied with a deceased fMRI signal for primed versus unprimed stimuli in various brain regions, often called “repetition suppression”, or RS. Previous studies proposed that RS in posterior regions is associated with priming of perceptual processes, whereas RS in more anterior (prefrontal) regions is associated with priming of conceptual processes. To clarify which regions exhibit reliable RS associated with perceptual and conceptual priming, we conducted a quantitative meta-analysis using coordinate-based activation likelihood estimation. This analysis included 65 fMRI studies that i) employed visual repetition priming during either perceptual or conceptual tasks, ii) demonstrated behavioral priming and iii) reported the results from whole-brain analyses. Our results showed that repetition priming was mainly associated with RS in left inferior frontal gyrus and fusiform gyrus. Importantly, RS in these regions was found for both perceptual and conceptual tasks, and no regions show RS that was selective to one of these tasks. These results question the simple distinction between conceptual and perceptual priming, and suggest consideration of other factors such as stimulus-response bindings.